Komunikasi Data Berbasis Protokol UDP pada Sistem Ubiquitous Mobile Sensing Kualitas Sumber Air - Yuning Widiarti Darsono; Adianto Adianto; Mirna Apriani (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
The need for monitoring, effective and efficient control and evaluation of water quality in regional waters Surabaya become a demand for population growth, climate change and variability in the current era of urbanization. The traditional method is done by collecting water samples, test and analyze water in the laboratory has been relatively expensive and do not have the ability to capture real-time data, analysis and information delivery fast in making decisions. On the other hand, the rapid spread in the use of mobile phones in developing countries has increased mobile data management applications. A variety of mobile applications has also increased in recent years. This is because mobile phones cheap, easy to use and can transmit multiple types of information including images and GPS data remotely. In this paper, the author describes a data communication system of water quality resources based on UDP protocol. This system is called ubiquitous mobile sensing consisting of microcontroller Arduino, water quality sensors, and Android smartphones. It has the ability to detect temperature, dissolved oxygen (DO), pH and electrical conductivity (EC) in real time. By using this monitoring system, the data result is expected more accurate, faster and cheaper.